The Determination of an Affective, Cognitive and Conative Measure of Consumer Ethnocentrism - Teoh, Kenny Guan Cheng (2007)
As a measure of consumer ethnocentrism, CETSCALE has aroused great interest in the field of consumer behaviour. However, despite CETSCALE's popularity, there is sufficient theoretical evidence to support investigating its content validity. Various authorities have questioned the purity of the scale, i.e., its lack of domain specificity; In particular, the items that comprise CETSCALE seem to be indicative of other phenomena such as patriotism, protectionism, and even xenophobia! Consequently, this study addresses CETSCALE's lack of domain specificity by proposing a theoretically sound psychometric scale that is 1) true to Sumner's (1906) definition of consumer ethnocentrism, 2) embraces Rosenberg and Hovlands' (1960) 3- Component View of Attitude model, and 3) faithful to Churchill's (1979) Paradigm for Developing Better Measures of Marketing Constructs. Volumes one, two and three of Marketing Scales Handbook (American Marketing Association)-comprising 1,647 psychometric scales-were used as the oracle, from which was derived an initial pool of 249 items. Based on a sample of 803 respondents, these items were subjected to factor analysis (exploratory and confirmatory), finally giving rise to the 14-item scale TRUCET scale. TRUCET scale has good psychometric properties, consistently demonstrating construct validity in various tests of discriminance and convergence. Its predictability has also been demonstrated in a nomological framework with related constructs. And it meets the requirements of face validity. The results indicate TRUCET scale to be domain specific. It presents researchers with an alternative measure of consumer ethnocentrism which is untainted with foreign artefacts.